Formation of multifunctional ZrO2–MgO-hBN nanocomposite for enhanced bone regeneration and E coli bacteria filtration applications - Hussain A.; Gautam C.; Jafri A.; Mishra V.K.; Madheshiya A.; Gautam A.; Singh M.K.; Gautam R.K.; Gupta M.; Arshad M.; Vajtai R.; Ajayan P.M. (My University, 2025)
Due to adequate properties, bone implant materials have attracted much attention to repair the large-sized bone fractures which cannot be auto-healed. Recently, three-dimensional (3-D) nanocomposites were synthesized using two-dimensional (2-D) materials which reveals unexpected performances. In the present study, 3-D mesoporous biocomposites were developed for bone/dental implant applications. A ternary novel biocomposite system ZrO2–MgO-hBN was fabricated with low density, high strength, and mesoporous interconnected architecture using conventional bottom-up synthesis method. Due to remarkable stability in different fluids such as water, minimum essential medium eagle-alpha modification (α-MEM), acids and oils, the fabricated biocomposites displayed multifunctional activities along with suitable proliferation of osteoblast like MG63 cell and filtration of Escherichia coli (E-coli) bacteria from the water. Moreover, the biocomposite exhibited protective nature from harmful ultraviolet (UV) radiation. A new phase of hexagonal boron nitride (h-BN) in the form of highly porous nanotubes was observed that opens the new possibility to optimize the synthesis of porous h-BN nanotubes to explore their further applications. Therefore, based on mechanical, tribological and biological performances, the nanocomposite is a biomimetic material having potential as bone/dental implant and can be used for multifunctional applications. © 2020 Elsevier Ltd and Techna Group S.r.l.